P842 SARS-CoV-2 antibody titers analysis in immune mediated inflammatory disease patients after COVID-19 vaccination: a monocentric retrospective study. (30th January 2023) - Delaleeuwe, I; Aoun, J; Hoyois, A; Brasseur, C; Di Romana, S; Muls, V
Abstract: Background: Immune-mediated inflammatory diseases (IMID) including inflammatory bowel diseases (IBD) and inflammatory arthritides are commonly treated with biological therapies, in particular anti-TNF. Patients on anti-TNF have impaired protective immunity following pneumococcal, influenza and viral hepatitis. However, the serological response to COVID-19 vaccination is still under-studied. Recent studies demonstrated that serologic response is attenuated in IMID patients on immunosuppressive therapy. In this study, the primary outcome is to describe the antibody response in IMID patients according to baseline patient characteristics, type of inflammatory disease, treatment and disease activity. Secondary outcome is to compare antibody response in patients treated with anti-TNF, versus other biologic therapies. Methods: This study is a monocentric retrospective study, including 265 IMID patients followed at CHU Saint Pierre, Belgium, between 2021 and 2022. Respective baseline patient characteristics, vaccination status, treatment type, disease activity and SARS-CoV-2 antibody titers (IgG) after first, second and third vaccination were collected and analyzed. Results: A total of 265 patients were enrolled (mean age 47 years old, 35% males, 67% IBD patients). Of these, 217 patients (82%) completed the 2 doses of vaccination and 130 patients (49%) the 3 doses, while 40 patients (15%) remained unvaccinated. Antibody titers after 2 doses of vaccination were available for 50 patients. In this group, the median antibody titer was 93 AU/mL [26-421] after first vaccination, raised up to 640 AU/mL [271-800] after the second vaccination (Δ85%, p<0.0001). Similarly, a statistically significant increase was noted in the subgroup of patients with available serologic data after 3 vaccination doses (N=18). The median antibody titer after the first vaccination in anti-TNF subgroup (N=15) was lower than that in other biotherapies subgroup (N=23); 34 AU/mL [6-145] versus 131 AU/mL [34-704] respectively. However, after the second vaccination, higher antibody titers were found in the anti-TNF subgroup, 686 AU/mL [321-800] versus 400 AU/mL [250-800] (p<0.388). Conclusion: In our cohort of IMID patients, followed at CHU Saint Pierre, Belgium, there was a statistically significant raise in antibody titers after the second and third dose of COVID-19 vaccination, regardless of the type of inflammatory disease, disease activity, type of treatment and vaccine type. The antibody titers in this particular immunocompromised population were comparable to that found in the literature for the general population. More prospective observational studies are needed with a larger sample size to determine the characteristics of patients with sub-optimal serological response.